Dendriform pulmonary ossification in patient with rare earth pneumoconiosis. Issue 8 (1st August 2005) - Yoon, H K; Moon, H S; Park, S H; Song, J S; Lim, Y; Kohyama, N
Abstract : The case history is presented of a patient with pathologically proven dendriform pulmonary ossification and rare earth pneumoconiosis confirmed by analytical transmission electron microscopy. This is thought to be the first report of this association.